World Bank Research Digest, Vol. 10(3) - World Bank (World Bank, Washington, DC, 2016)
This issue includes the following headings: The Social Determination of Behavior; Social Norms and Development Economics; Behavioral Insights to Improve Development Policy; Overcoming Behavioral Constraints in Access to Social Programs; Changing Rural Sanitation Behavior in India; Improving the Impact of Financial Education; and Using Cognitive Behavioral Therapy to Reduce Crime and Violence.